Microbial Selenium-Enriched Bacterial Fertilizer: Biofortification Technology to Boost Pea Sprout Quality and Selenium Content - Yaqi Wang; Ying Li; Yu Wu; Yang Liu; Yadong Chen; Yanlong Zhang; Xiangqian Jia (Agronomy)
Selenium-enriched vegetables are a safe way to combat selenium deficiency in humans. Here, a new microbial selenium-enriched bacterial fertilizer (named “HJ”) was prepared and studied by dipping, and then its application strategy was optimized and compared with other commercially available selenium fertilizers. The results showed that the application of HJ selenium fertilizer to peas by soaking (Se concentration 10 μg/mL) and foliar application (Se concentration 8 μg/mL) could effectively enhance their growth, selenium enrichment ability, stress tolerance and nutritional quality. In particular, the selenium content of peas in the HJ-treated group exhibited a significant increase of 69.86% in comparison with the control group. Moreover, HJ treated pea sprouts demonstrated enhanced antioxidant activity, as well as elevated levels of vitamin C and protein, amongst other observations. The findings of this study offer novel insights into the development of eco-friendly selenium fertilizers and provide guidance for optimal fertilizer application techniques.